Exploring Motivation of Engineering Students in Face-to-Face and Hybrid Learning Environments in Finland: A Qualitative Analysis - Özgül, Aslihan (My University, 2024)
This master’s thesis explores the factors influencing the motivation of engineering students in both face-to-face and hybrid learning environments at a University of Applied Sciences in Finland, and what kind of support the students perceive would sustain and improve their motivation. As engineering students face increasing demands for high skill levels and competencies in social and innovation areas, understanding their motivation is crucial for their success in completing their degrees. Using the Situated Expectancy-Value Theory by Eccles and Wigfield as theoretical framework, this research centers around six male engineering students pursuing the same degree in a face-to-face and hybrid learning environment. The study uses a qualitative research approach, with semi-structured interviews, to capture detailed personal factors and experiences influencing their motivation. The findings reveal how individual experiences, such as the personal interest and significance of their studies, career aspirations, learning environments and interactions with instructors, shape their motivation. Further, the analysis identifies a range of support mechanisms that students wish for, from institutional policies and their instructors. The findings underscore the critical role of motivation among the interviewed engineering students and highlight the need for support and improvements in the current educational practices.
Keywords: Engineering Education, Motivation, Situated Expectancy-Value Theory, Learning Environment, Finnish Higher Education